Reclaimed identity; a restaurant and dwellings in Klövsjö - Tegay, Anna (My University, 2024)
With the increase in mountain tourism, visitors from all over the country and world travel to the scenic landscapes of northern Sweden to experience its nature during different seasons of the year. However, the high demand leads to an increased exploitation of the historic environments of the mountain villages. By exploring the concept of identity, delving into the theories of critical regionalism, and studying traditional building techniques, this thesis aims to synthesize these elements into a design that strikes a balance between honoring local identity and embracing change without resorting to imitation and historization. The central question explored is how a design proposal for a restaurant and dwellings in the mountain area of Klövsjö can be informed by the local identity. The project unfolds across three phases; theoretical studies, site analysis and design iterations, resulting in a design proposal. The project is situated in a small village named Klövsjö, located in the southern parts of Jämtland. On top of being a well-frequented destination for hiking, cross country and alpine skiing, the entire village of Klövsjö is part of a larger area of national interest for cultural environmental protection. Adjacent to Svartåstjärnen, the project site serves as a transitional space between the public amenities of the ski village and the private housing area, resulting in the mixed program of the project. Informed by the principles of log construction, the design proposal utilizes various techniques in accordance to the specific program of each building. These techniques range from demanding and robust log timbering methods to more lightweight versions that challenge traditional norms, creating a dialogue between tradition and innovation. The thesis concludes with a reflection on the malleable nature of the concept of identity, with its significance lying not in rigid definition but rather in the contemplation of it. By crafting spaces that honor the past while embracing the future, weaving together elements of tradition, innovation, and local identity, the project seeks to create spaces that spark dialogue and evoke thoughtful consideration of the context.